A study of employee acceptance of artificial intelligence technology - Youngkeun Choi (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - This study aims to reveal the role of artificial intelligence (AI) in the context of a front-line service meeting to understand how users accept AI technology-enabled service. Design/methodology/approach - This study collected 454 Korean employees through online survey methods and used hierarchical regression to test the hypothesis empirically. Findings - In the results, first, clarity of user and AI's roles, user's motivation to adopt AI-based technology and user's ability in the context of the adoption of AI-based technology increases their willingness to accept AI technology. Second, privacy concerns related to the use of AI-based technology weakens the relationship between role clarity and user's willingness to accept AI technology. And, trust related to the use of AI-based technology strengthens the relationship between ability and user's willingness to accept AI technology. Originality/value - This study is the first one to reveal the role of AI in the context of a front-line service meeting to understand how users accept AI technology-enabled service.
Keywords: 650; Ability; Artificial intelligence; Clarity of role; Motivation; Willingness to accept AI technology